From autonomy to heteronomy of design. Evolutionary contributions of technological design - Losasso, Mario; Tersigni, Enza (TECHNE - Journal of Technology for Architecture and Environment, 2021)
The position of the project between autonomy and heteronomy is constantly echoed both in current prevalent thought and in the transformations of the ontology of the project. Contemporary pluralism and multiculturalism foster a shift in the interest of design debate towards a convergence of knowledge and expertise with different points of view. Technological culture of design provides its own contribution interpreting the project as a moment of coordination between diversified and complex inputs within the building process at a time when the development in the field of collaborative digital systems opens up to new directions for research in architecture and renewed conditions of heteronomy in the project.